Adultery - Coelho, Paulo; Costa, Margaret Jull;Perry, Zoe (New York : Vintage Books, 2014)
In the latest novel from #1 best-selling author Paulo Coelho, a married woman in her thirties attempts to overcome midlife ennui by rediscovering herself in a passionate relationship with a man who had been her high school boyfriend.
Keywords: LITERARY FICTION